OP0001 Effect of Secukinumab, An Interleukin-17a Inhibitor, on Spinal Radiographic Changes through 2 Years in Patients with Active Ankylosing Spondylitis: Results of The Phase 3 Study, Measure 1. (15th July 2016) - Braun, J.; Baraliakos, X.; Deodhar, A.; Baeten, D.; Sieper, J.; Emery, P.; Talloczy, Z.; Martin, R.; Richards, H.B.
Abstract : Background: Inhibition of radiographic spinal changes, which are primarily osteoproliferative in nature in active ankylosing spondylitis (AS), represents a main goal of therapy. Objectives: To assess the effects of secukinumab on radiographic progression up to 104 weeks (wks) in the MEASURE 1 trial (NCT01358175 ). Methods: In MEASURE 1, 371 patients (pts) with active AS were randomized to secukinumab or placebo (pbo). Pts on secukinumab received a 10 mg/kg intravenous (i.v.) loading dose at baseline (BL), Wks 2 and 4, and then 150 or 75 mg subcutaneously (s.c.) every 4 wks (q4w) from Wk 8. Pbo was given on the same schedule. Pbo pts were re-randomized to secukinumab 150 or 75 mg s.c. q4w based on ASAS20 response at Wk 16 (non-responders switched at Wk 16; responders at Wk 24). Lateral radiographs of the cervical and lumbar spine performed at BL and Wk 104 were read centrally applying the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). Two independent readers, blinded to treatment arm and radiograph sequence, scored the images. Pts initially randomized to secukinumab, who had x-rays available at BL and Wk 104 (n=168), were included in this analysis. Observed data are shown. Results: Secukinumab data were pooled for both the 150 mg and 75 mg doses as there were no major differences in radiographic results between the two doses. At BL, 104/168 (62%) pts had syndesmophytes, 105/168 (63%) had elevated (>5 mg/L) CRP levels, 42/168 (25%) were smokers, and 123/168 (73%) were male. The mean (±SD) mSASSS at BL was 10.22±16.62; mean change from BL at Wk 104 was 0.30±2.53. Approximately 80% of pts showed no radiographic progression (mSASSS change ≤0) from BL to Wk 104 (Figure ). At Wk 104, new syndesmophytes were found in 3/64 (5%) pts who were without syndesmophytes at BL. Approximately 70% of pts with syndesmophytes at BL developed no additional syndesmophytes through Wk 104. Overall, BL mSASSS and mean mSASSS change at Wk 104 were higher in males (mean change 0.38±2.79 vs 0.08±1.58 in females), those with BL syndesmophytes (0.47±3.20 vs 0.02±0.26 in pts with no BL syndesmophytes), or elevated CRP levels at BL (0.47±2.66 vs 0.02±2.27 in pts with normal CRP levels). There were no major differences between the secukinumab only and pbo→secukinumab groups in terms of mSASSS change through Wk 104. Inter- and intra-reader agreement on mSASSS scores was 85% (Kappa 0.70) for both. Conclusions: In secukinumab-treated pts, the mean change in mSASSS was low, with no major difference between doses. Changes were higher in pts who were male, had BL syndesmophytes, or elevated BL CRP. No radiographic progression was observed in ∼80% of the pts receiving secukinumab over 104 wks. This is the first report of interleukin-17A inhibition on structural changes in patients with AS. Acknowledgement: The study was sponsored by Novartis Pharma AG. Disclosure of Interest: J. Braun Grant/research support from: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis and UCB, Consultant for: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis and UCB, Speakers bureau: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis and UCB, X. Baraliakos Grant/research support from: AbbVie, Merck, Pfizer, UCB, Novartis, and Chugai, Consultant for: AbbVie, Merck, Pfizer, UCB, Novartis, and Chugai, Speakers bureau: AbbVie, Merck, Pfizer, UCB, Novartis, and Chugai, A. Deodhar Grant/research support from: AbbVie, Amgen, Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Consultant for: AbbVie, Amgen, Boehringer Ingelheim, Janssen, Novartis, Pfizer, UCB, D. Baeten Grant/research support from: Boehringer Ingelheim, Janssen, MSD, Novartis, Pfizer, Consultant for: AbbVie, Boehringer Ingelheim, BMS, Eli Lilly, Janssen, MSD, Novartis, Pfizer, Roche, UCB, J. Sieper Grant/research support from: AbbVie, Boehringer Ingelheim, Janssen, Novartis, Merck, Lilly, Pfizer, and UCB, Consultant for: AbbVie, Boehringer Ingelheim, Janssen, Novartis, Merck, Lilly, Pfizer, and UCB, P. Emery Consultant for: AbbVie, BMS, Merck, Novartis, Pfizer, Roche, UCB, Z. Talloczy Shareholder of: Novartis, Employee of: Novartis, R. Martin Shareholder of: Novartis, Employee of: Novartis, H. Richards Shareholder of: Novartis, Employee of: Novartis